Bryophytes of Kédougou (Eastern Senegal), with a key to the Fissidens of Senegal. (2nd January 2018) - Diop, Djibril; Diop, Doudou; Bruggeman-Nannenga, Maria Alida; Samba Mbaye, Mame; Noba, Kandioura; Hedenäs, Lars; Gradstein, S. Robbert; Reeb, Catherine; Vanderpoorten, Alain
Abstract : The bryophyte flora of the Sahelian region of sub-Saharan Africa is characterized by a low species richness, but is also extremely poorly documented. We present here the results of a floristic survey in Kedougou (eastern Senegal), which yielded 22 species. Two liverworts and 15 moss species are new to the country, so that the bryophyte flora of Senegal now includes a total of 4 liverwort and 34 moss species. An identification key is provided for Fissidens, which, with eight species, is the richest moss genus of the country.